2018
DOI: 10.1016/j.pmedr.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Health behavior practice among understudied Chinese and Filipino Americans with cardiometabolic diseases

Abstract: Lifestyle modification and health behavior practice among the individuals with cardiometabolic diseases (CMD) are important for secondary prevention and disease control. This study was designed to investigate and compare health behavior practices among Chinese and Filipino Americans with CMD. Three hundred seventy-four Asian Americans (211 Chinese and 163 Filipino) who reside in the greater Philadelphia region and had either CMD or no identified disease were included in the study. Information on smoking, alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Filipino adults have been found to get lower amounts of physical activity than White adults [ 8 ] and to have a higher prevalence of smoking than Chinese adults [ 7 ]. A survey of Chinese and Filipino adults residing in the Philadelphia, PA, area found that low percentages were following recommended guidelines for fruit and vegetable consumption, use of salt, consumption of sweets, and physical activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Filipino adults have been found to get lower amounts of physical activity than White adults [ 8 ] and to have a higher prevalence of smoking than Chinese adults [ 7 ]. A survey of Chinese and Filipino adults residing in the Philadelphia, PA, area found that low percentages were following recommended guidelines for fruit and vegetable consumption, use of salt, consumption of sweets, and physical activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven included studies adopted a cross‐sectional design (Bi et al, 2014; Chen et al, 2013; Chen et al, 2014; Hu et al, 2013; Huang, Zhang, et al, 2011a; Lee et al, 2018; Modesti et al, 2019; Newson et al, 2013; Qin et al, 2014; Zhang et al, 2013; Zhang et al, 2016), two were experimental studies (Huang, Hu, et al, 2011b; Zou et al, 2014) and one was a qualitative phenomenological approach (Zou, 2019). The included studies were conducted in China ( n = 10), USA ( n = 1), Italy ( n = 1) and Canada ( n = 1), and one was a multi‐national study from which only the findings for the Chinese cohort were included in the review (Newson et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings corroborate that hyperlipidaemia is associated with higher risks of CAD, overweight or obesity, and hypertension. 7 Lifestyle changes such as a healthy diet, physical activity or exercise, and smoking cessation are needed to reduce CMD risk factors. Estimates indicate that 44% of the decrease in CAD death rates were due to changes in CAD-related lifestyle and behavioural factors, including improved smoking rates, physical inactivity, and regulation of systolic blood pressure and total cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Specifically, a study among Chinese and Filipino Americans reported that the increasing number of premature deaths in lowand middle-income countries is attributable to the suboptimal implementation of prevention strategies by healthcare providers to reduce CAD risk factors such as hypertension, diabetes, elevated cholesterol, tobacco use, overweight/obesity-also referred to as cardiometabolic diseases (CMD). 7 Likewise, increased risk for CAD is also associated with poor access to effective and equitable healthcare services (including early detection services) in individuals from these countries. 3,8 Older adults are at greater risk for CAD and CMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation